2017
DOI: 10.4085/1062-6050-52.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Trainers' Reasons for and Mechanics of Documenting Patient Care: A Report From the Athletic Training Practice-Based Research Network

Abstract: Context:  Documenting patient care is an important responsibility of athletic trainers (ATs). However, little is known about ATs' reasons for documenting patient care and the mechanics of completing documentation tasks. Objective:  To understand ATs' perceptions about reasons for and the mechanics of patient care documentation. Design:  Qualitative study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 13 publications
1
47
2
Order By: Relevance
“…The research team, which comprised 6 ATs who had various levels of experience with the CQR tradition, was described in an earlier study. 16…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The research team, which comprised 6 ATs who had various levels of experience with the CQR tradition, was described in an earlier study. 16…”
Section: Designmentioning
confidence: 99%
“…Training procedures for the CORE-AT EMR have been described. 16 Data saturation was confirmed after the inclusion of 10 ATs who met the predetermined criteria. Participants were 4 men and 6 women (age ¼ 32.6 6 11.4 years, athletic training experience ¼ 7.1 6 7.8 years).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these results indicate that ATs may spend a considerable amount of time managing nontimeloss injuries due to the greater volume and amount of care associated with nontime-loss injuries compared with timeloss injuries. Further, in ongoing investigations 23,24 aimed at understanding ATs' documentation habits, the researchers reported that ATs were more likely to formally document time-loss injuries, possibly due to their perceived significance and severity, than nontime-loss injuries within the patient-documentation portion of an EMR. We noted that only 37.7% of all current injury encounters were associated with an injury that was formally documented within the patient-documentation portion of the EMR.…”
Section: Discussionmentioning
confidence: 99%
“…23 Despite these potential benefits, it is evident that ATs do not comprehensively document care and use EMRs to their full capacity. [24][25][26] Several groups have analyzed patient care documentation in athletic training, particularly for injury surveillance. For example, researchers have used the National Collegiate Athletic Association Injury Surveillance Program and High School Reporting Information Online system for a decade to describe the injury and exposure data of athletes participating in 13 collegiate and high school sports.…”
mentioning
confidence: 99%